WIRED FOR GOD strategic technology planning for non profits - Joni Podolsky (Jossey-Bass, 2003)
AT ITS BROADEST level, a technology plan is a communications tool. Its purpose is to provide a framework for improving an organization’s effectiveness through the implementation of appropriate tools. The plan is a document that aligns an agency’s technology use with its strategic goals, defines what technology will be implemented and how it will be implemented, and determines how the technology will be supported over time.AT ITS BROADEST level, a technology plan is a communications tool. Its purpose is to provide a framework for improving an organization’s effectiveness through the implementation of appropriate tools. The plan is a document that aligns an agency’s technology use with its strategic goals, defines what technology will be implemented and how it will be implemented, and determines how the technology will be supported over time.